Phylogeographic diversity and hybrid zone of Hantaan orthohantavirus collected in Gangwon Province, Republic of Korea. - Geum-Young Lee; Won-Keun Kim; Kyungmin Park; Seung-Ho Lee; Jusun Hwang; Jin Sun No; Seungchan Cho; Daesang Lee; Dong-Hyun Song; Se Hun Gu; Man-Seong Park; Seong Tae Jeong; et al. (Public Library of Science (PLoS), 2020)
Background Hantaan orthohantavirus (Hantaan virus, HTNV), harbored by Apodemus agrarius (the striped field mouse), causes hemorrhagic fever with renal syndrome (HFRS) in humans. Viral genome-based surveillance at new expansion sites to identify HFRS risks plays a critical role in tracking the infection source of orthohantavirus outbreak. In the Republic of Korea (ROK), most studies demonstrated the serological prevalence and genetic diversity of orthohantaviruses collected from HFRS patients or rodents in Gyeonggi Province. Gangwon Province is a HFRS-endemic area with a high incidence of patients and prevalence of infected rodents, ROK. However, the continued epidemiology and surveillance of orthohantavirus remain to be investigated. Methodology/principal findings Whole-genome sequencing of HTNV was accomplished in small mammals collected in Gangwon Province during 2015-2018 by multiplex PCR-based next-generation sequencing. To elucidate the geographic distribution and molecular diversity of viruses, we conducted phylogenetic analyses of HTNV tripartite genomes. We inferred the hybrid zone using cline analysis to estimate the geographic contact between two different HTNV lineages in the ROK. The graph incompatibility based reassortment finder performed reassortment analysis. A total of 12 HTNV genome sequences were completely obtained from A. agrarius newly collected in Gangwon Province. The phylogenetic and cline analyses demonstrated the genetic diversity and hybrid zone of HTNV in the ROK. Genetic exchange analysis suggested the possibility of reassortments in Cheorwon-gun, a highly HFRS-endemic area. Conclusions/significance The prevalence and distribution of HTNV in HFRS-endemic areas of Gangwon Province enhanced the phylogeographic map for orthohantavirus outbreak monitoring in ROK. This study revealed the hybrid zone reflecting the genetic diversity and evolutionary dynamics of HTNV circulating in Gangwon Province. The results arise awareness of rodent-borne orthohantavirus diseases for physicians in the endemic area of ROK.